2016
DOI: 10.1093/ageing/afw202
|View full text |Cite
|
Sign up to set email alerts
|

Prospective association between late-life physical activity and hospital care utilisation: a 7-year nationwide follow-up study

Abstract: Background: It is still equivocal whether there is a potential role of late-life physical activity in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Our results are in line with other econometric studies, which also found that higher levels of physical activity were associated with lower healthcare use or costs in population based samples [15,16,21,22]. Ku et al and Carlson et al also reported similar percentage differences in healthcare expenditure.…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with other econometric studies, which also found that higher levels of physical activity were associated with lower healthcare use or costs in population based samples [15,16,21,22]. Ku et al and Carlson et al also reported similar percentage differences in healthcare expenditure.…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 92%
“…Ku et al and Carlson et al also reported similar percentage differences in healthcare expenditure. [16,22] Karl et al used objective measures of physical activity in addition to self-reported physical activity, although the accelerometer data were only available for a subsample. [16] The authors reported that the accelerometer measured physical activity affected healthcare costs but no effect was found for the association with self-reported physical activity in line with our findings, in a comparable sample of European adults aged 48 to 68 years old.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…However, many research findings indicate that individuals are likely to reduce their healthcare utilization as they become older [ 24 , 25 ]. Although positive relationships between age and healthcare demand have also been found [ 26 ]. Older adults expect healthcare to be comprehensive, desiring psychological and emotional care more than physical attention [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher value in BMI in women probably would indicate their vulnerability to chronic diseases such as hypertension and diabetes. In the literature, it has been shown that gender is a strong predisposing factor that influences healthcare utilization, and females are more likely than males to seek healthcare, especially in their later life [ 16 , 26 ]. In Sri Lanka, females outlive males, and older women experience greater ill health and loss of activities of daily living as they age [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These non-disease specific outcome measures can be used to examine the overall level of health service usage [20]. Ageing populations put ever-increasing pressure on health care services and it is therefore important to establish if modest differences in modifiable lifestyle behaviours such as physical activity are related to hospitalisation [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%